The Atypical Protein Kinase C Small Molecule Inhibitor ζ-Stat, and Its Effects on Invasion Through Decreases in PKC-ζ Protein Expression - Smalley, Tracess; Metcalf, Rainer; Patel, Rekha; Islam, S. M. Anisul; Bommareddy, Raja Reddy; Acevedo-Duncan, Mildred (Frontiers in Oncology, 2020)
Ovarian cancer is estimated to reach 22,530 diagnoses and cause 13,980 cancer deaths per year. The most common histology diagnosed of ovarian cancer is epithelial ovarian carcinomas. An aggressive epithelial subtype is CCOC and is characterized as a non-serous ovarian cancer. Protein kinase C is an enzymatic family of proteins that have been found to be a component in cancer progression, tissue invasion, and metastasis. The atypical PKC isoforms, PKC-ι and PKC-ζ, have been suggested to participate in the increased proliferation of ovarian cancers. Previous studies have indicated that novel aPKC inhibitors ICA-1S and ζ-Stat decreased the migratory behaviors of colorectal cancer cells and were selective for PKC-ι/λ and PKC-ζ, respectively. The aims of this investigation were to further determine the binding mechanisms of ζ-Stat, expand on the tissue range of these compounds, investigate the therapeutic potential of ζ-Stat in CCOC, and to illustrate the disruption of invasion via the PKC-ζ signaling cascade. The methods utilized were molecular docking and virtual target screening, Western blot analysis, end-point PCR, GST pull down, cell viability and invasion and migration assays. We discovered that the small molecule inhibitor, ζ-Stat, is a prospective drug candidate to investigate as a novel potential treatment for CCOC. We also found that the PKC-ζ/Ect2/Rac1 activation pathway was decreased by ζ-Stat, which in turn decreased invasive behavior of CCOC.